The Influence of Social Media Marketing Adoption, Information Quality and Digital Culture on Political Engagement - Dea Ananda Tanan; Rahmad Solling Hamid; Muhammad Iqbal (Journal of Applied Business, Taxation and Economics Research, 2026)
Study This aim For analyze influence social media marketing adoption , quality information , and digital culture towards involvement political Generation Z in Padang Sappa Subdistrict , Palopo City , with use approach quantitative through analysis multiple linear regression . Test results show that instrument study has fulfil criteria validity and reliability , with Cronbach's Alpha value is above 0.6 . Findings study indicates that third variables independent influential positive and significant to involvement politics , good in a way partial and simultaneous . Coefficient value determination (R²) of 0.729 indicates that amounting to 72.9% variation involvement political can explained by the adoption of social media marketing, quality information , and digital culture . Among third variables said , digital culture becomes the most dominant factor in influence involvement politics , which emphasizes that generation active young people interacting in digital spaces tends to own level awareness and participation more politics​ high . In terms of overall , results study This confirm importance role of social media , quality information , and digital culture in form participation political Generation Z in the era of digital democracy.